Optical Coherence Tomography and Coronary Dissection: Precious Tool or Useless Surplus? - Barbieri, Lucia; D’Errico, Andrea; Avallone, Carlo; Gentile, Domitilla; Provenzale, Giovanni; Guagliumi, Giulio; Tumminello, Gabriele; Carugo, Stefano (Frontiers in Cardiovascular Medicine, 2022)
Spontaneous coronary artery dissection (SCAD) is a rare clinical condition, but frequently manifested as acute myocardial infarction. In this particular setting, in recent years, optical coherence tomography (OCT) has been established as a possible diagnostic method due to the high spatial resolution (10–20 μm), which can visualize the different layers of coronary vessels. OCT can better analyze the “binary” or double lumen morphology, typical of this entity. Furthermore, it can identify the entrance breach and the circumferential and longitudinal extension of the lesion. However, we have to emphasize that this technique is not free from complications. OCT could further aggravate a dissection or exacerbate a new intimal tear. Therefore, the use of OCT in the evaluation of SCAD should be defined by balancing the diagnostic benefits versus procedural risks. Moreover, we underline that as SCAD is a rare condition and OCT is a recently introduced technique in clinical practice, limited data is available in literature.